Evaluation of the effect of denture cleansers on the surface roughness of hard denture base material: An In vitro study - Jinal Barochia; Sujatha Kamath (Wolters Kluwer Medknow Publications, 2018)
Background: Maintaining the oral hygiene of denture wearers is a challenge faced in modern dentistry. Biofilm formed on dentures has been associated with denture stomatitis, malodor, aspiration pneumonia, infectious endocarditis, gastrointestinal infection, and chronic obstructive pulmonary disease. Objective: The purpose of this study was to evaluate the effect of denture cleansers on the surface roughness of hard denture base material. Materials and Methods: A total of 100 heat-cure acrylic resin specimens were fabricated with dimensions 30 mm × 15 mm × 3 mm in length, width, and thickness, respectively. All specimens were distributed into four groups randomly. Three commonly prescribed denture cleansers were used for immersion in this study. Regular tap water was used for immersion in the control group. Surface roughness was determined before immersion and after immersion in denture cleansing solutions using contact profilometer. The data were subjected to statistical analysis using paired t-test, one-way analysis of variance, and Tukey's multiple post hoc test. Results: The change in surface roughness of acrylic samples immersed in Clanden group was statistically significant (P < 0.05) at individual group level. However, the change in surface roughness of acrylic samples after immersion, when compared between the groups, namely, control, Clinsodent, Clanden, and Fittydent, was not statistically significant (P > 0.05). Conclusion: Within the limitation of this study, the three denture cleansing materials, namely, Clinsodent powder, Clanden tablet, and Fittydent tablet, are safe to be prescribed as denture cleansers.